Exploring the Relationships Between Counseling Students' Cultural Factors, Academic Aptitude, and Self‐Efficacy. (1st December 2019) - Oh, Seungbin; Hahs‐Vaughn, Debbie L.; Hagedorn, Bryce
Abstract : The authors explored the pattern of change in counseling students' ( N = 373) counseling self‐efficacy (CSE) throughout their program and the influence of identifying variables. Results indicated that specific factors significantly predicted students' initial CSE levels and the rate of CSE change. Implications for future research and counselor education programs are presented.